In Vivo Inflammatory Effects of Ceria Nanoparticles on CD-1 Mouse: Evaluation by Hematological, Histological, and TEM Analysis - Anna Poma; Anna Maria Ragnelli; Joaquin de Lapuente; David Ramos; Miquel Borras; Pierpaolo Aimola; Mario Di Gioacchino; Sandro Santucci; Laura De Marzi (Journal of Immunology Research)
The attention on CeO2-NPs environmental and in vivo effects is due to their presence in diesel exhaust and in diesel filters that release a more water-soluble form of ceria NPs, as well as to their use for medical applications. In this work, acute and subacute in vivo toxicity assays demonstrate no lethal effect of these NPs. Anyhow, performing in vivo evaluations on CD-1 mouse systems, we demonstrate that it is even not correct to assert that ceria NPs are harmless for living systems as they can induce status of inflammation, revealed by hematological-chemical-clinical assays as well as histological and TEM microscope observations. TEM analysis showed the presence of NPs in alveolar macrophages. Histological evaluation demonstrated the NPs presence in lungs tissues and this can be explained by assuming their ability to go into the blood stream and lately into the organs (generating inflammation).